Culture and domination: cultural relationship between Brazil and the US during the cold war - Tota, Antônio Pedro (Universidade Estadual Paulista / UNESP, 2007)
Anti-Communist culture and political trend shaped the western hemisphere, after World War II. Brazil played in import role in the United States foreign policy for Latin America. During the Cold War time people from Brazil listened radio program broadcasted in a kind of hook up which main goal was to show the advantages of liberalism over nationalistic policy.